PERKEMBANGAN MADRASAH PASCA UNDANGUNDANG NOMOR 20 TAHUN 2003 TENTANG SISTEM PENDIDIKAN NASIONAL DALAM BINGKAI PENELITIAN - Nuruddin Nuruddin (Sekretariat Badan Litbang dan Diklat Kementerian Agama RI, 2014)
This paper attempts to investigate madrasah in line with the 5 year momentum of madrasa (2004-2009) coincided with the enactment of the National Education System Act No. 20 of 2003. Hence, this is to portray the madrasa after the birth of the Act. Madrasah has a clear position that is equal to that of public schools. Madrasah can be viewed from five elements, such as, namely, access, quality, relevance and competitiveness, and management and governance. Further this also describes the demands that the madrasa have to be more active in self-portraying as the best educational institutions with competitive advantages, and being able to build an extensive network. In this regard, Madrasa must first be able to overcome some common problems, such as lack of human resources, lack of infrastructure, limited funds, traditional management, and so forth.